Preparation and characterization of modified graphene oxide/polyethersulfone positively charged hybrid nanofiltration membrane - Yu, L.; Zhang, Y.; Liu, Jian (Jilin Daxue,Jilin University, 2014)
Graphene oxide (GO) has received tremendous attention thanks to its unique two-dimensional feature, fantastic mechanical and chemical properties. In this paper, GO was fabricated and then was modified by chitosan. After the quaternization of modified GO, the positively charged material was used as inorganic additive to prepare polyethersulfone (PES) hybrid nanofiltration membrane with phase inversion method using N, N-dimethylacetamide (DMAc) as solvent, polyvinylpyrrolidone (PVP) as pore-forming agent. The effect of modified GO content on the separating property of hybrid membranes was investigated. The results suggested that the positively charged nanofiltration membranes were prepared successfully without the changes of morphology. With the increase of modified GO content, the water flux and separation selectivity of hybrid membranes were improved significantly and it was proposed that the best additive quantity of modified GO was round 0.5% (mass fraction).